Molecular analysis and genotype‐phenotype correlation of Diamond‐Blackfan anemia. Issue 2 (27th December 2017) - Arbiv, O.A.; Cuvelier, G.; Klaassen, R.J.; Fernandez, C.V.; Robitaille, N.; Steele, M.; Breakey, V.; Abish, S.; Wu, J.; Sinha, R.; Silva, M.; Goodyear, L.; et al.
Abstract : Diamond‐Blackfan anemia (DBA) features hypoplastic anemia and congenital malformations, largely caused by mutations in various ribosomal proteins. The aim of this study was to characterize the spectrum of genetic lesions causing DBA and identify genotypes that correlate with phenotypes of clinical significance. Seventy‐four patients with DBA from across Canada were included. Nucleotide‐level mutations or large deletions were identified in 10 ribosomal genes in 45 cases. The RPS19 mutation group was associated with higher requirement for chronic treatment for anemia than other DBA groups. Patients with RPS19 mutations, however, were more likely to maintain long‐term corticosteroid response without requirement for further chronic transfusions. Conversely, patients with RPL11 mutations were less likely to need chronic treatment. Birth defects, including cardiac, skeletal, hand, cleft lip or palate and genitourinary malformations, also varied among the various genetic groups. Patients with RPS19 mutations had the fewest number of defects, while patients with RPL5 had the greatest number of birth defects. This is the first study to show differences between DBA genetic groups with regards to treatment. Previously unreported differences in the rate and types of birth defects were also identified. These data allow better patient counseling, a more personalized monitoring plan, and may also suggest differential functions of DBA genes on ribosome and extra‐ribosomal functions. Abstract :